Greater contribution of low-nutrient tolerance to sorghum and maize growth under combined stress conditions with high aluminum and low nutrients in solution culture simulating the nutrient status of tropical acid soils - Akhter, A; Khan, S.H.; Hiroaki, E; Tawaraya, K; Rao, Idupulapati M.; Wenzl, Peter; Ishikawa, S.; Wagatsuma, Tadao (Informa UK Limited, 2009)
Aluminum is usually regarded as the determining factor for plant growth in acid soils and nutrient deficiencies are often additional growth-limiting factors in tropical acid soils. Taking into account the potential interactions between Al toxicity and nutrient deficiencies, the present study investigated sorghum (Sorghum bicolor Moench [L.]) and maize (Zea mays L.) cultivar differences for: (1) Al tolerance (relative growth in a one-fifth strength nutrient solution [low-nutrient medium, ionic strength: 4.5 mmol L?1] with Al and without Al), (2) low-nutrient tolerance (relative growth in a low-nutrient medium compared with growth in a full-strength nutrient solution), (3) combined tolerance (relative growth in a low-nutrient medium containing Al compared with a full-strength medium lacking Al). The goal of the present study was to identify the predominant growth-limiting factor using a solution culture medium that simulates the nutrient status of tropical acid soils. Differential Al tolerance among 15 cultivars of sorghum and 10 cultivars of maize in short-term assays (2.5 or 20 µmol L?1 AlCl3 in 0.2 mmol L?1 CaCl2 at pH 5.0 or 4.9, respectively, for 24 h) was positively correlated with Al tolerance in long-term cultures (11.1 or 42.6 µmol L?1 soluble Al in the low-nutrient medium at pH 4.5 or 4.3, respectively, for 29 days). However, the level of Al tolerance in the short-term assays was not correlated with the combined tolerance, suggesting that a short-term screening technique may not be practically useful for estimating cultivar adaptation to a combination of stress factors in tropical acid soils. In sorghum, a less Al-tolerant plant species, higher Al tolerance was associated with less Al absorption by the roots and greater K translocation into the shoots. In maize, a more Al-tolerant plant species, there was no correlation between the accumulation or transport of elements and Al tolerance. Standardized partial regression coefficients suggested that low-nutrient tolerance contributed more to combined tolerance than Al tolerance under most conditions (except for Al-sensitive sorghum at 42.6 µmol L?1 AlCl3). A greater combined tolerance was associated with a higher K shoot concentration in sorghum and a higher Ca shoot level in maize. Plant nutritional characteristics linked to low-nutrient tolerance should be evaluated as an important strategy for plant production in tropical acid soils, both for Al-tolerant plant species and for Al-sensitive plant species under low-Al conditions.